2012
DOI: 10.1128/ec.00054-12
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Host Ligands Correlates with Colocalization of Gal/GalNAc Lectin Subunits in Lipid Rafts and Phosphatidylinositol (4,5)-Bisphosphate Signaling in Entamoeba histolytica

Abstract: bEntamoeba histolytica is an intestinal parasite that causes dysentery and liver abscess. Parasite cell surface receptors, such as the Gal/GalNAc lectin, facilitate attachment to host cells and extracellular matrix. The Gal/GalNAc lectin binds to galactose or N-acetylgalactosamine residues on host components and is composed of heavy (Hgl), intermediate (Igl), and light (Lgl) subunits. Although Igl is constitutively localized to lipid rafts (cholesterol-rich membrane domains), Hgl and Lgl transiently associate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 54 publications
2
25
0
Order By: Relevance
“…We previously demonstrated that membrane fractions 9 to 14 possess high levels of cholesterol and contain lipid rafts (31). Less buoyant fractions (fractions 17 to 19) and the pellet fraction (fraction 20) are actin rich (26,28,31). Similar to the enrichment seen in mammalian cells, we observed an enrichment of PI(4,5)P 2 in lipid rafts (fractions 9 to 14) ( Fig.…”
Section: Resultssupporting
confidence: 71%
See 4 more Smart Citations
“…We previously demonstrated that membrane fractions 9 to 14 possess high levels of cholesterol and contain lipid rafts (31). Less buoyant fractions (fractions 17 to 19) and the pellet fraction (fraction 20) are actin rich (26,28,31). Similar to the enrichment seen in mammalian cells, we observed an enrichment of PI(4,5)P 2 in lipid rafts (fractions 9 to 14) ( Fig.…”
Section: Resultssupporting
confidence: 71%
“…1A). We previously demonstrated that membrane fractions 9 to 14 possess high levels of cholesterol and contain lipid rafts (31). Less buoyant fractions (fractions 17 to 19) and the pellet fraction (fraction 20) are actin rich (26,28,31).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations